STUDENTS’ POINTS OF VIEW ON ONLINE AND OFFLINE LANGUAGE LEARNING SYSTEMS - Ittaqullah; Hesthi Herusatoto (Conscientia, 2021)
The Covid-19 outbreak has forced students to study from home and switched from offline learning to online learning. This study inquired about the preferences and opinions of language school students majoring in English towards online and offline learning. The students filled out a questionnaire at the end of the second semester of their fully online classes. The results indicate that they preferred the combination of online and offline learning and favored face-to-face more than online learning when they worked in groups. They also tended to prefer offline classes to learn the productive skill of speaking. The receptive skill of listening was deemed to be best taken online.  Offline classes were still considered to be easier to complete and help them perform better than online classes which they thought to have lower course depth and quality and more difficult tests and activities.